Scaling climate smart agriculture technologies through collaborative innovation - Nzuki, Esther; Nduah, Alex; Ogutu, Liz (2024)
The partnership between AICCRA, Lewa Wildlife Conservancy, and the African Conservation Tillage Network has greatly promoted the access and adoption of CSA and CA technologies among the small-scale farmers to enhance soil health, water retention, and on-farm biodiversity conservation. Training programs and demonstration plots have empowered thousands of farmers, promoting sustainable livelihoods and resilience to climate shocks. These collaborative efforts emphasize ecosystem-based adaptation and align with Kenya’s sustainable development goals and Vision 2030